Modulation of gut microbiome in response to the combination of Escherichia coli Nissle 1917 and sugars: a pilot study using host-free system reflecting impact on interpersonal microbiome - Heer, Kiran; Kaur, Manpreet; Sidhu, Dwinder; Dey, Priyankar; Raychaudhuri, Saumya (Frontiers in Nutrition, 2024)
The differential effects of probiotic, prebiotic, and synbiotic formulations on human health are dictated by the inter-individual gut microbial profile. The effects of probiotics such as Escherichia coli Nissle 1917 (ECN) on gut microbiota may vary according to the microbiome profiles of individuals and may be influenced by the presence of certain carbohydrates, which can impact microbial community structure and treatment results.Method: Processed fecal samples from donors having contrasting lifestyles, dietary patterns, and disease histories were mixed with 5×10 6 CFU/mL ECN with or without 1% (w/v) sugars (glucose, galactose, or rice starch) in a host-free system. Post-incubation, 16s rRNA sequencing was performed. Microbial diversity and taxonomic abundance were computed in relation to the probiotic, prebiotic, and synbiotic treatment effects and interpersonal microbiome variance.Result: Baseline gut microbial profiles showed significant inter-individual variations. ECN treatment alone had a limited impact on the inter-personal gut microbial diversity and abundance. Prebiotics caused a substantial enrichment in Actinobacteria, but there were differences in the responses at the order and genus levels, with enrichment shown in Bifidobacterium, Collinsella, and Megasphaera. Subject B exhibited enrichment in Proteobacteria and Cyanobacteria, but subject A showed more diversified taxonomic alterations as a consequence of the synbiotic treatments. Despite negligible difference in the -diversity, probiotic, prebiotic, and synbiotic treatments independently resulted in distinct segregation in microbial communities at the -diversity level. The core microbiota was altered only under prebiotic and synbiotic treatment. Significant correlations primarily for minor phyla were identified under prebiotic and synbiotic treatment.The interindividual microbiome composition strongly influences the effectiveness of personalized diet and treatment plans. The responsiveness to dietary strategies varies according to individual microbiome profiles influenced by health, diet, and lifestyle. Therefore, tailored approaches that consider individual microbiome compositions are crucial for maximizing gut health and treatment results.